Безопасный уровень напряженности электромагнитного поля при контактной сварке - Левченко, О.Г.; Левчук, В.К. (Автоматическая сварка, 2008)
Выполнен анализ источников и формы сигналов магнитных полей, создаваемых оборудованием при контактной сварке, с целью их достоверной гигиенической оценки в соответствии с нормативами. Предложены рекомендации по защите сварщиков от магнитных полей. Sources and shapes of signals of the magnetic fields, generated by resistance welding equipment, have been analyzed to perform their reliable hygienic evaluation in line with new standards of Ukraine. Results of investigations of spectral composition and intensity of the magnetic fields, generated using different resistance welding methods, are presented. Recommendations for protection of welders against magnetic fields are suggested.